(3ZQGFH GdMedGJ GdUdjHjIs (3ceG hQOJ aj ePcQGJ LfhOgGs - (3eGcGj, JTGQdRs; (3GdUGhj, Cceds; (3UdGM, eQhIs; (3OGQ GdMhGOjJ ddfTQ hGdJhRjYs ((3GdefhajI, eUQs (3OGQ MhGOjJ ddfTQ hGdJhRjYs, 2024)
(3eGcGj jYQV cja Cf GdMThO ef eNJda GdWHbGJ GdGLJeGYjI, HOkAG ef GdaQSGf GdfHdGA Edi GdadGMjf GdHSWGA, GfOaYhG fMh GdCQGVj GdebOSI GSJLGHI ddOYhGJ GdOjfjI hGdTYGQGJ GdJj cGfJ JQhL dgG GdcfjSI(B. (3cGf ojfXQ Edi gPg GdMQhH Ydi CfgG LgGO ebOS, hcGf ojYJbO Cf ef jTGQc ajgG SjMUd Ydi eZaQI ddNWGjG hecGaBJ QhMjI hCMjGkfG ecGSH eGOjIs
Keywords: (3GdMedGJ GdUdjHjIs -- (3ChQhHGs -- (3GdYUhQ GdhSWis; (3ChQhHGs -- (3JGQjNs -- (3GdYUhQ GdhSWis